Use of an NLP tool applied to the detection of cyberbullying on Twitter - Aguirre Soto, Jonathan Matwey (2022)
This paper will briefly overview how the constant development of information and communication technologies (ICTs) has changed the interaction between people today. Real experiences have been transferred to a virtualized method, in this case, the internet. Although the space-time barriers of traditional communication have been fragmented, social relations have become more assertive, but new problems related to different behaviors arise. Bullying is defined as an act that threatens the well-being of a person and becomes cyberbullying when it is carried out over the internet, generating large-scale problems of anxiety, depression, and even the act of suicide, which is why it is essential to detect these malicious behaviors in time. We will use a Natural Language Processing (NLP) tool using Twitter as the basis for the extraction of knowledge bases.